Epidemiology of Traumatic Brain Injury in Neurosurgery Department of Tertiary Referral Hospital at North Sumatera, Indonesia - Tandean, Steven; Japardi, Jeffrey; Kollins, Fini; Loe, Michael Lumintang (Medicinus, 2019)
Introduction : Traumatic brain injury (TBI) is the most common problem that caused morbidity and mortality in the world. Epidemiology information of TBI is very important in understanding the causes and the risk factors of TBI, so that effective programs can be designed to prevent injury. This study purposed to provide overview of TBI pattern in tertiary referral hospital at North Sumatera with focus on epidemiological data of TBI pattern. Methods : The design of this study is a retrospective, and it is done in general hospital H. Adam Malik from June-December 2018 with sample from all patient with traumatic brain injury that admited in hospital. All medical records with diagnosis traumatic brain injury will be assessed for several variables as age, gender, etiology, severity, length of stay and outcome. Results : During the period of study, 118 patients with traumatic brain injury were admitted in neurosurgery ward. The highest TBI cases was occurs in male patients with range age between 18-35 years old, and caused by traffic accident. Most patients admitted to Emergency department with GCS 13-15 and epidural hematoma was the most common lesion found in head CT scan. Length of stay in this research mostly between 1-5 days,  and  the mortality rate is about 16.9%, which is dominated by severe head injury. Conclusions : Head injury mostly found in male with productive age, and traffic accident be the most common caused. Severe head injury still have quite high mortality rate.